Methods of Mathematical Economics : Linear and Nonlinear Programming, Fixed-Point Theorems - Franklin, Joel N. ((Classics in Applied Mathematics ;)
Aplicaciones matemáticas a la economía. Contenido: Programación lineal; Programación no lineal; Teorema del punto fijo.